GILBERT'S SYNDROME IN CHILDREN: CONTEMPORARY DIAGNOSTIC POTENTIALITIES - I.N. Zakharova; M.I. Pykov; Z.V. Kaloeva; L.A. Kataeva; S.V. Shishkina; I.V. Berezhnaya; E.V. Reznichenko; N.V. Molotkova (Union of pediatricians of Russia, 2011)
Gilbert's syndrome is a benign indirect hyperbilirubinemia of the hereditary nature, caused by deficiency of the enzyme uridindiphosphatglucuronitransferase. UGT1A1 gene is localized on chromosome 2q37. The most common is a defect in the promoter region of the gene pairs in the thymine-adenin. 200 children aged 8 to 16 years with clinical and laboratory manifestations of Gilbert syndrome have been examined. All children undergone to a genetic study. It was calculated that the external signs, the shown complaints and laboratory manifestations are not enough sensitive and specific. This suggests that these symptoms can not be used as criteria for diagnosis of the Gilbert syndrome. The obtained results allow to recommend that all children with hyperbilirubinemia and Gilbert's syndrome suspected should undergo to a genetic research as a priority.Key words: liver, hyperbilirubinemia, Gilbert syndrome, gene UGT1A1, diagnosis, children.